Numerical Analysis of Submerged Horizontal Plate Wave Energy Converter Device Considering Float Effects - Rodrigo Costa Batista; Marla Rodrigues de Oliveira; Elizaldo Domingues dos Santos; Luiz Alberto Oliveira Rocha; Liércio André Isoldi; Mateus das Neves Gomes (Fluids)
This study proposes a three-dimensional numerical wave tank (NWT) to calculate wave propagation and hydrodynamic forces based on the Navier–Stokes equation, using commercial Computational Fluid Dynamic (CFD) software ANSYS Fluent. The VOF Method is utilized to identify the free surface. The CFD model employed for generating waves in the NWT is initially verified using analytical theory to evaluate the accuracy of the results. In addition, the User-Defined Function (UDF) in ANSYS Fluent is implemented to ensure the model performs under the oscillatory conditions of the Submerged Horizontal Plate (SHP) Wave Energy Converter (WEC) device, which is localized at the center of the NWT. Finally, the influence of SHP oscillation on the device’s average efficiency was analyzed by comparing seven cases with different geometric configurations, considering both the oscillating and non-oscillating conditions of the SHP under the incidence of different waves. The results indicated that the geometric configuration and wave conditions of Case 4 achieved the best performance, reaching an average efficiency of 35.68%.